Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé